Effects of carbohydrate quantity and glycaemic index on central fatigue during endurance exercise / Khong Teng Keen - Khong , Teng Keen (2017)
Central fatigue (CF) is the inability of the central nervous system to generate or maintain activation of muscle, measured using neurophysiological techniques such as twitch-interpolation techniques via nerve stimulation and neural responses recording of muscle activity. Reduction of muscle force alongside central activation has been associated with hypoglycaemia, indicating importance of carbohydrate (CHO) in preventing CF; one possible mechanism is through attenuation of serotonin, a neurotransmitter associated with sense of tiredness, produced during exercise when free-fatty acid (FFA) is high. In addition, the quality of CHO, categorised by glycaemic index (GI), influences fuel selection during exercise. Low GI (LGI) could improve endurance exercise by providing steady supply of CHO due to lower insulin response which promotes fat oxidation compared to high GI (HGI). While peripheral benefits of CHO are well-documented, only few studies measured CF with neurophysiological techniques. The objective of this study was to investigate the effects of pre-exercise meals with different quantity and GI of CHO on CF. The neurophysiological measures employed were voluntary activation (VA), central-activation ratio (CAR) obtained during maximal voluntary contraction (MVC), alongside related variables, i.e. resting twitch and Mmax, blood serotonin, FFA, and insulin. To elucidate the effects CHO and GI, three studies were designed; the first aimed at verifying the custom-made meals’ post-prandial blood glucose (BG) response to conform with the established norm, the second investigated the effects of high and low CHO meals on CF following a 90-minute endurance exercise, while the third distinguished HGI and LGI on CF following similar exercise. The first study, using a randomised, cross-over design with a 7-day washout-period, ten participants’ post-prandial BG responses were analysed after consuming two sets of iv meals: i) iso-caloric high CHO (HCHO, 1.5 g/kg body weight) and low CHO (LCHO, 0.8 g/kg body weight); and ii) iso-macronutrients; high CHO (1.5 g/kg body weight) with high (~75) and low (~40) GI. Consistent with the literature, HCHO and HGI meals induced a higher BG area-under-curve (AUC) compared to LCHO and LGI, respectively. In study-2, fourteen participants, in a cross-over, randomised, double-blind design, consumed either HCHO or LCHO meals 1-hour prior to a 90-minute run at 65% VO2max. HCHO preserved MVC post-running, mirrored by preservation of CAR and VA as well as an unchanged serotonin level. LCHO meanwhile showed lower insulin response (indicating lipolysis), and marked MVC loss with concurrent reduction in CAR and VA as well as increased serotonin. Study-3 employed similar study design and found that with HGI meal, MVC was better maintained compared to LGI, but without concomitant changes in VA and serotonin, despite the differences in fuel selection. The results do suggest that HGI maintains the force production by larger magnitude compared to LGI due to preservation of CAR. The difference seen could be attributed to fuel availability as HGI provide higher CHO oxidation for MVC. In conclusion, HCHO better attenuates CF compared to LCHO meal; and when amount of CHO is similar between meals, HGI better maintained CF following a 90-minute run compared to LGI meal.